ASSESMEN PORTOFOLIO DALAM PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN DASAR KOGNITIF DAN KEMAMPUAN BAHASA ANAK - Handayani, Ni Nyoman Lisna (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This study uses an experimental research pattern The Posttest-Only Control-Group Design. The research population is all children of group B TK Lab Undiksha. The sample in this study amounted to 41 people. Data on children's basic cognitive abilities and language skills were collected by observation using an observation sheet. The data analysis used was MANOVA (Multivariat Analysis of Variance) assisted by SPSS 17.00 for windows. The results showed that: First, portfolio assessment in contextual learning had an effect on students' cognitive abilities (F= 28.56 p<5%). Second, portfolio assessment in contextual learning has an effect on students' language skills (F= 38.75 p<5%). Third, portfolio assessment in contextual learning has a significant effect on students' basic cognitive abilities and language skills (F= 17.59 p<5%).